Ireland : Financial Sector Assessment Program: Technical Note-Nonbank Sector Stability Analyses. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2016)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for Ireland in the areas of nonbank sector stability. Both nonparametric and parametric methods suggest that the residential real estate market in Ireland is close to or moderately below its equilibrium level. Two standard metrics of price-to-income and price-to-rent ratios show that following a protracted period of overvaluation prior to the crisis and a correction afterward, the market has been close to its equilibrium level in recent quarters. Households have deleveraged, but are still highly indebted. The stability analysis results also suggest that vulnerabilities among nonfinancial firms have moderated in recent years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet